2015
DOI: 10.1002/ase.1543
|View full text |Cite
|
Sign up to set email alerts
|

Students helping students: Evaluating a pilot program of peer teaching for an undergraduate course in human anatomy

Abstract: The educational literature generally suggests that supplemental instruction (SI) is effective in improving academic performance in traditionally difficult courses. A pilot program of peer teaching based on the SI model was implemented for an undergraduate course in human anatomy. Students in the course were stratified into three groups based on the number of peer teaching sessions they attended: nonattendees (0 sessions), infrequently attended (1‐3 sessions), and frequently attended (≥ 4 sessions). After contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
3
37
0
2
Order By: Relevance
“…Furthermore, previous studies have demonstrated that students provide positive feedback about peer teaching (Goode et al, ; Furmedge et al, ; Agius et al, ), near‐peer teaching (Evans and Cuffe, ; Durán et al, ; Nelson et al, ; Rosenberg et al, ), and reciprocal peer‐teaching programs (Manyama et al, ). Moreover, beyond their gains in knowledge, students show improvement in understanding and retaining the material presented, improvement in study habits, more positive attitudes toward the subject, and independent self‐learning (Manyama et al, ; Bruno et al, ; Hanson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have demonstrated that students provide positive feedback about peer teaching (Goode et al, ; Furmedge et al, ; Agius et al, ), near‐peer teaching (Evans and Cuffe, ; Durán et al, ; Nelson et al, ; Rosenberg et al, ), and reciprocal peer‐teaching programs (Manyama et al, ). Moreover, beyond their gains in knowledge, students show improvement in understanding and retaining the material presented, improvement in study habits, more positive attitudes toward the subject, and independent self‐learning (Manyama et al, ; Bruno et al, ; Hanson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Near peer teaching (NPT) is a similar variant, in which higher level students (tutors typically 2-5 years ahead of the tutee in the academic program) mentor their junior classmates (tutees) by temporarily assuming the role of the instructor. Therefore, implementing an NPT program within an undergraduate curriculum stands to prepare medical students for their future role as educators.We have read with great interest the recent article published in ASE by Bruno et al (2016), and we applaud their work; however, as the authors mentioned, there were several limitations. In the United Kingdom, the General Medical Council's guidelines, Tomorrow's Doctors: Recommendations on Undergraduate Medical Education, states that a medical graduate must "function effectively as a mentor and teacher" (GMC, 2009).…”
mentioning
confidence: 98%
“…In the United Kingdom, the General Medical Council's guidelines, Tomorrow's Doctors: Recommendations on Undergraduate Medical Education, states that a medical graduate must "function effectively as a mentor and teacher" (GMC, 2009). Therefore, implementing an NPT program within an undergraduate curriculum stands to prepare medical students for their future role as educators.We have read with great interest the recent article published in ASE by Bruno et al (2016), and we applaud their work; however, as the authors mentioned, there were several limitations. We agree that the sample size and the number of sessions involved were too small to draw any longstanding conclusions.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Students who receive tutoring from peers also report improvements in understanding, interpersonal skills and study habits. (Lockspeiser et al, 2008;Manyama et al, 2016) In addition to the reported benefits of peer tutoring there are numerous accounts of improved learning outcomes for students who participate in workshops designed for active learning (Gonsalvez et al, 2015;Bruno et al, 2016;Saavedra et al, 2016;Scott et al, 2017). Active learning aims to enable students to participate in a range of activities designed to help them think critically about the content and apply it to reallife situations.…”
Section: Introductionmentioning
confidence: 99%